Waste-Derived Nanoparticles: Synthesis Approaches, Environmental Applications, and Sustainability Considerations - Abdelbasir, Sabah M.; McCourt, Kelli M.; Lee, Cindy M.; Vanegas, Diana C. (Frontiers in Chemistry, 2020)
For the past few decades, a plethora of nanoparticles have been produced through various methods and utilized to advance technologies for environmental applications, including water treatment, detection of persistent pollutants, and soil/water remediation, amongst many others. The field of materials science and engineering is increasingly interested in increasing the sustainability of the processes involved in the production of nanoparticles, which motivates the exploration of alternative inputs for nanoparticle production as well as the implementation of green synthesis techniques. Herein, we start by overviewing the general aspects of nanoparticle synthesis from industrial, electric/electronic, and plastic waste. We expand on critical aspects of waste identiﬁcation as a viable input for the treatment and recovery of metal- and carbon-based nanoparticles. We follow-up by discussing different governing mechanisms involved in the production of nanoparticles, and point to potential inferences throughout the synthesis processes. Next, we provide some examples of waste-derived nanoparticles utilized in a proof-of-concept demonstration of technologies for applications in water quality and safety. We conclude by discussing current challenges from the toxicological and life-cycle perspectives that must be taken into consideration prior to scale-up manufacturing and implementation of waste-derived nanoparticles.